The Impact of Vitamin K2 (Menaquionones) in Children's Health and Diseases: A Review of the Literature - Agnieszka Kozioł-Kozakowska; Katarzyna Maresz (MDPI AG, 2022)
Vitamin K2 activates vitamin K-dependent proteins that support many biological functions, such as bone mineralization, the inhibition of vascular stiffness, the improvement of endothelial function, the maintenance of strong teeth, brain development, joint health, and optimal body weight. Due to the transformation of food habits in developed countries over the last five decades, vitamin K and, specifically, vitamin K2 intakes among parents and their offspring have decreased significantly, resulting in serious health implications. The therapeutics used in pediatric practice (antibiotics and glucocorticoids) are also to blame for this situation. Low vitamin K status is much more frequent in newborns, due to both endogenous and exogenous insufficiencies. Just after birth vitamin K stores are low, and since human milk is relatively poor in this nutrient, breast-fed infants are at particular risk of a bleeding disorder called vitamin K deficiency bleeding. A pilot study showed that better vitamin K status is associated with lower rate of low-energy fracture incidence. An ongoing clinical trial is intended to address whether vitamin K2 and D3 supplementation might positively impact the biological process of bone healing. Vitamin K2 as menaquinone-7 (MK-7) has a documented history of safe and effective use. The lack of adverse effects of MK-7 makes it the ideal choice for supplementation by pregnant and nursing women and children, both healthy and suffering from various malabsorptions and health disorders, such as dyslipidemia, diabetes, thalassemia major (TM), cystic fibrosis (CF), inflammatory bowel diseases (IBD), and chronic liver diseases. Additionally, worthy of consideration is the use of vitamin K2 in obesity-related health outcomes.